Pelatihan Desain Media Pembelajaran Berbasis ICT - Dinar Riaddin; Fahruh Juhaeva; Djaffar Lessy; Yuli Hastuti; Rhaishudin Jafar Rumandan (IAIN AMBON, 2022)
The purpose of the information and communication technology-based learning media design training is to improve the skills of teachers in making teaching materials using powerpoint media and making quiz questions, assignments, or exams using the wondershare quiz creator media. The methods used in the service are training and workshops. The subjects in this training were teachers of MTs Negeri 4 Maluku Tengah and MA Negeri 3 Maluku Tengah. After this training, the teacher participating in the activity got additional insight into the use of powerpoint media and the Wondershare Quiz Creator application and was also skilled in using both media. Keywords: learning media, information dan communication technology, powerpoint, wondershare quiz creator.